Incommensurable or inexorable?: Comparing the economic, ecological, and social values of exchanged multiple use lands. (May 2018) - Jenkins, Jeffrey
Abstract: Land exchanges are a process increasingly being used by state government and private industry to facilitate extractive development on lands bounded within or contiguous to federal public lands. These swaps were originally intended as a legal tool to reconfigure property ownership in a contiguous pattern and thereby align land use, management, and conservation priorities. However, in doing so access to locally significant multiple use activities, like hunting as is the case here, end up redistributed to properties that have different levels of ecological and social value that are not necessarily integrated into the economic value of exchanged lands. The Bearlodge land exchange, occurred between state and private lands in two different areas of the Black Hills National Forest and was undertaken by Rare Element Resources Ltd. in coordination with the State of Wyoming to obtain ownership of a state section adjacent to the mine's lease on U.S. Forest Service land. The acquisition of the adjacent section was deemed necessary by the mining corporation to collocate a waste tailing pile next to the mine. In this case, the different types of value - economic, social, and ecological - are individually assessed and collectively compared between exchanged lands using a mixed methods approach. Findings demonstrate that while exchanges may be roughly equivalent in constructed economic value, the social and ecological components underpinning assessed property value in the trade are inequivalent due to differences in place-based connections of recreational amenities and the ecological composition unique to each parcel. Highlights: Develops a framework to compare land value through an assessment of property, plant diversity, and big game hunting. Offers insight for local, state, and federal agency policy makers involved in land exchanges. Provides a cautionary and critical take on the incommensurability of economic, ecological and social value types.